Mortal Engines (Predator Cities) - Philip Reeve (London Marion Lloyd Books, 2012)
MORTAL ENGINES launched Philip Reeve's brilliantly-imagined creation, the world of the Traction Era, where mobile cities fight for survival in a post-apocalyptic future.The first instalment introduces young apprentice Tom Natsworthy and the murderous Hester Shaw, flung from the fast-moving city of London into heart-stopping adventures in the wastelands of the Great Hunting Ground.